Ensuring postgraduate paediatric curriculum delivery: a novel approach. (29th September 2015) - Hodgkinson, R; Roueche, A; Klaber, R; Cunnington, F; Watson, M
Abstract : Aim: The Royal College of Paediatrics and Child Health (RCPCH) has introduced detailed specialty specific postgraduate curricula to specify the learning needs of trainees. There is a requirement to ensure trainees are able to attain these competencies through local educational provision and quality assurance is overseen by the Postgraduate Medical and Education Training Board. In our school, trainees are expected to gain exposure to these competencies in the workplace, and by attending regional training days to supplement their learning. Methods: In 2008, the school established a curriculum delivery subgroup to consider how trainees could best meet the curriculum objectives. The subgroup developed a novel approach to consider which curriculum topics could be achieved in the workplace, through local NHS Trusts, and which required additional training. The curriculum subgroup, consisting of Training Programme Directors and trainee representatives, initially identified which topic areas were likely to be achieved by the majority of trainees within the workplace. The remaining topics were put before the wider school forum, consisting of forty-four college tutors and trainee trust representatives. An automated response system allowed attendees to vote on which topics were achieved by the majority of trainees in the workplace, and which topics needed additional educational support. The immediacy of results allowed discussion of discrepancies among the group, and for votes to be re-cast. Finally, an online survey tool was developed to obtain a wider consensus from educational supervisors and trainee representatives from across the region. Results: Competencies identified as inconsistently covered by the majority of trainees in the workplace were then tabulated and the curriculum delivery sub group researched existing educational opportunities which fulfilled the learning objectives. Where gaps remained, new resources have been commissioned to provide opportunities for trainees to meet the curricula requirements. Conclusions: This extensive piece of work, mapping how trainees can meet RCPCH curriculum objectives has now been adopted by three other schools in the UK. Our method of obtaining a broad consensus from a mix of experienced trainers and trainees, has helped focus regional resources to provide training for curriculum topics that are hardest to achieve in the workplace.